Latvijas Universitātes izlaidumi fotoliecībās - Livdāne, Sarmīte; Ločmele, Annija; Latvijas Universitātes Muzejs (My University, 2020)
Latvijas Universitātes Muzejs par godu izlaidumu sezonai piedāvā iepazīt Latvijas Universitātes Muzeja Latvijas Universitātes vēstures kolekcijās, Latvijas Universitātes foto arhīvā un personīgajos foto albumos esošās izlaiduma fotogrāfijas. Izlaidums universitātē ir svinīgs akts, kur visi vienas fakultātes studiju programmu absolventi pēc veiksmīgi nokārtotiem gala pārbaudījumiem un studiju noslēguma darba aizstāvēšanas saņem Latvijas Universitātes diplomus. Tradicionāli izlaidumi norisinās Alma Mater sirdī (Lielajā aulā) skaistākajā vasaras laikā jūnijā un jūlijā.

In honor of the graduation season, the Museum of the University of Latvia offers to get acquainted with the graduation photos in the history collections of the Museum of the University of Latvia, the photo archive of the University of Latvia and personal photo albums. Graduation in the University of Latvia is a solemn act, where all graduates of the study programs of one faculty receive University of Latvia diplomas after successfully passing the final examinations and defending the final thesis. Traditionally graduations take place in the heart of the Alma Mater (Great Hall) during the most beautiful summer months in June and July.
Graduations of the University of Latvia in photos
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; izlaidumi; svētki; Latvijas Universitāte; fotogrāfijas; graduations; holidays; University of Latvia; photos